Features of statistical analysis of medical-psychological research - Ivanchuk Марія; Polishchuk Олександр (Psychosomatic Medicine and General Practice, 2020)
The purpose of the study: to consider the features of statistical analysis in psychological and medical-psychological research. Results. One of the features of psychological research is the process of measuring the results of the experiment. Unlike medical research, which typically uses physical units of measurement, most variables in psychological research are not unambiguous or easy to measure. To describe the procedures of psychological measurement in psychological research four types of measurement scales are used: nominative, ordinal, interval, and scale of equal relations. Statistical analysis of the results of medical and psychological research depends on the type of scale in which the studied trait was measured. The nominative scale is a scale that classifies by name. Conjugacy tables are used to describe and analyze nominative scales. An ordinal scale is a scale that classifies on the principle of "more or less". Statistical analysis of ordinal scales is performed using non-parametric criteria. The interval scale is a scale according to which each of the possible values ​​of the feature is at the same distance from the other value. The scale of equal relations has all the properties of nominative, ordinal, and interval scales. To analyze the results of the study, which were measured in interval scales or in scales of equal relations, one uses parametric or nonparametric criteria depending on the distribution of a random variable. Conclusions. The choice of method of statistical analysis of the results of psychological research depends on the type of scale in which the data were measured.